Vitamin D Deficient Older Adults Are More Prone to Have Metabolic Syndrome, but Not to a Greater Number of Metabolic Syndrome Parameters - Pott-Junior, Henrique (Nutrients, 2020)
This study investigated the relationship between metabolic parameters and low serum 25-hydroxyvitamin D (25(OH)D) levels in older adults (n = 265). They were assessed for anthropometrics and metabolic measurements, including 25(OH)D, insulin, glucose, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and other inflammatory markers. Vitamin D deficiency was defined as a 25(OH)D level below 50 nmol/L. Comparisons between groups were performed using Wilcoxon–Mann–Whitney or Pearson’s Chi-squared test. A multivariate adjusted Poisson regression was used to model the number of metabolic parameters as a function of a set of explanatory variables. Subjects with 25(OH)D deficiency were predominantly females and presented higher body weight, body mass index, waist circumference, triglycerides and Tumor Necrosis Factor-α (TNF-α), and higher insulin resistance. Metabolic syndrome was also more prevalent among 25(OH)D-deficient subjects. In those without metabolic syndrome, 25(OH)D deficiency was related only to obesity and higher insulin resistance. Female sex, hypertension, higher waist circumference and higher levels of hemoglobin A1C (%), HDL-C, and TG were significantly associated with an increased number of metabolic syndrome parameters after adjusting for covariates, but 25(OH)D was not. The fact that serum 25(OH)D concentration was inversely associated with metabolic syndrome and insulin resistance not only reaffirms the relevance to consider serum 25(OH)D concentration as an influencing factor for insulin resistance, but also the need to actively screen for hypovitaminosis D in all patients with this condition.